Strength profile in young male athletes from different sports - Buśko Krzysztof; Gajewski Jan; Mazur-Różycka Joanna; Michalski Radosław; Łach Patrycja (Sciendo, 2013)
Study aim: The aim of the present study was to determine a strength profile which characterizes young male athletes from different sports and to use the method of allometry to synthetically evaluate the muscular strength with respect to body mass.